2018
DOI: 10.1038/s41598-018-34888-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of differential vanadate sensitivity in two Ogataea species links protein glycosylation and phosphate transport regulation

Abstract: The closely related yeasts Ogataea polymorpha and O. parapolymorpha differ drastically from each other by sensitivity to the toxic phosphate analog vanadate. Search for genes underlying this difference revealed two genes, one designated as ABV1 (Alcian Blue staining, Vanadate resistance), which encodes a homologue of Saccharomyces cerevisiae Mnn4 responsible for attachment of mannosylphosphate to glycoside chains of secretory proteins, and the other designated as its S. cerevisiae homologue PHO87, encoding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The O. parapolymorpha strains used in this study ( Table 1 ) were constructed from the DL1-L strain ( leu2 ) [ 22 ] or its derivative DLdaduA ( leu2 ade2-Δ ura3::ADE2 ) [ 23 ]. The GEM-GECO expressing strain DL5 was obtained by transformation of DL1-L with the pKAM738 plasmid digested with BglII to facilitate its genome integration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The O. parapolymorpha strains used in this study ( Table 1 ) were constructed from the DL1-L strain ( leu2 ) [ 22 ] or its derivative DLdaduA ( leu2 ade2-Δ ura3::ADE2 ) [ 23 ]. The GEM-GECO expressing strain DL5 was obtained by transformation of DL1-L with the pKAM738 plasmid digested with BglII to facilitate its genome integration.…”
Section: Methodsmentioning
confidence: 99%
“…The PMC1 gene was inactivated in the O. parapolymorpha genome by replacement with either the LEU2 gene as described in [ 16 ] or Cre recombinase recognition sequence loxP as described in [ 24 ]. EcoRI-digested empty vectors pCHLX [ 22 ] or pCCUR1 [ 23 ] possessing LEU2 or URA3 gene as a selectable marker, respectively, were integrated into a unidentified genome locus when complementing leu2 or ura3 auxotrophic mutations was required. The O. polymorpha diploid strain, in which the CMD1 gene was inactivated, was obtained by crossing of 1B27-740G1M strain ( leu2 ade2 ura3::ADE2 { P MAL1 :GEM-GECO }) possessing the GEM-GECO expression cassette integrated into unidentified locus with the 1B/SM/C2LX4 strain ( leu2 ade2 mox::uPA [ LEU2 ]) possessing an autonomously replicating plasmid with the LEU2 selectable marker.…”
Section: Methodsmentioning
confidence: 99%
“…Michael's team has also shown that, unlike S. cerevisiae, H. polymorpha lacking both Golgi apparatus Ca 2+ /Mn 2+ ATPase Pmr1 and vacuolar Ca 2+ ATPase Pmc1, dies not due to excess of Ca 2+ in the cytosol but due to Ca 2+ shortage in the secretory pathway [32]. The most recent study by Michael's lab, involving H. polymorpha as a model organism revealed a link between protein glycosylation and phosphate transport [33].…”
mentioning
confidence: 99%